Women Participation in School Management Committee and Their Influence on Decision Making - Khadka, Tej Bahadur (Chaturbhujeshwar Academic Journal, 2023)
The women participation across diverse organizational landscape whether in socio-political or communal spheres is gradually increasing because of the constitutional provision in Nepal. Women participation in school management committee (SMC) is more crucial issue that is mandatory as a legal process however, realization of their effective role within SMCs proceedings remains somewhat elusive. Women could not still play an active role in decision where male domination is still remaining as a fossil. This research aims to explore the women participation in SMC and their role in decision making. This study is based on qualitative research design and phenomenological approach. The study area and participant selected purposively. From the field study, it is found that women members involve regularly in the meeting in time and participate in discussion but they have no information about the meeting agenda. As a result, they have no any agenda and preplan then they normally put their agenda but these could not be so strong and logical. Thus, the male domination starts from there and women's presence only for signature. They take women as an easy participant of the meeting because they do not disturb in any decision. Similarly, women do not believe themselves as a leader and psychologically think as weak and unable for leadership.